The effects of combined resisted and maximum velocity sprint training on the sprint performance of team sport players - Ward, C.; Ó Catháin, C.; Ní Chéilleachair, N.; Kelly, D. T. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The development of acceleration and maximum velocity (MV) sprint performance are key goals for field-based invasion team sport (FITS) coaches. Resisted sprint training (RST) has been shown to be an effective method for improving acceleration performance when using a broad range of loading magnitudes [1], yet there are concerns regarding the potential of `very heavy` loaded RST to negatively impact MV performance [2]. Alternatively, flying sprints are used by coaches when targeting MV improvements [3]. However, no research has investigated the efficacy of a concurrent RST and maximum velocity sprint training (MVST) protocol. This study aimed to determine the effectiveness of a combined RST and MVST approach on the in-season acceleration and maximum velocity performance of FITS players. METHODS: Elite level, male hurling players were assigned to an experimental group (EG) (n=21) or a control group (n=19). In addition to their regular training, the EG performed two sessions (1 x RST, 1 x MVST) per week for 8 weeks, while the control group performed unresisted sprinting (5-20m repetition distance range). RST was performed with a 50% Vdec load and a constant repetition distance of 15m, while MVST consisted of 8-12m flying sprints with a 25m build-up phase. Sprint, strength, and jump performance were measured at 1-week pre and post intervention. RESULTS: The EG displayed significant small within-group (pre to post) improvements in 5m (d = 0.57) and 10m (d = 0.44) split times, and MV (d = 0.35), while a significant moderate increase in SLJ performance (d = 0.89) was also found. A significant decrease in reactive strength (d = 0.42) and increase in relative strength (d = 0.53) were detected for the CG. Finally, there were significant time effects for first step flight time (FT) (p = 0.004) last step FT (p = 0.035), and the 10-20 m split time (p = 0.018). CONCLUSION: Performing a weekly combination of very-heavy RST and MVST across an 8-week in-season training block can yield improvements in both early acceleration and MV sprint performance. Additionally, study findings dampen previous concerns regarding the potentially negative impact of heavy-loaded RST on MV. Our study highlights the utility of this RST (using 8 sleds) and MVST approach within FITS settings, integrated prior to collective in-season sports training using a short 20-minute time slot.